Biological nature of human embryo. - Vescovi, A.L.; Spinardi, L. (Medicina e Morale, 2004)
The current debate on in vitro fertilization, the existence of an undetermined number of frozen human embryos and the possibility to clone living beings, including higher primates and humans, has raised a plethora of issues of both biological, ethical and, last but not least, legal nature. The debate has now heated around these issues and often results in utmost fierce confrontations, which are not solely confined to the stage provided by newspapers and television, but also involves institutional organs as well as the academic community. A common element in all of these discussions is the frequent lack of logical or scientific arguments to back up the contention(s) of some of the discussants. The debate then unfolds, based upon preconceived positions, the latter becoming ever more rigid, until the situation reaches a stalemate, strictly based on dogmatic, ideological or political views. This concise manuscript is meant to provide an objective, scientific review on the nature, identity and physiology of the most essential element around which all of these discussions revolve: the human embryo. This review aims at illustrating the various, progressive phases, through which human life develops, starting from the very initial stage - the fusion of the gametes (fertilization) - throughout the embryonic growth, until a mature human being is born. We hope that this document will provide matter for evaluation and study by those whom, for sake of knowledge and culture, or for their personal inner growth, devote themselves to the study of this topic of vital importance for mankind as a whole.